TINGKAT PENGETAHUAN PASIEN TENTANG PENYAKIT DIABETES MELITUS DENGAN TINDAKAN MENJAGA KESTABILAN GLUKOSA DARAH DI WILAYAH KERJA PUSKESMAS DUNGALIYO KABUPATEN DUNGALIYO - Fadli Syamsuddin; Asni Ayuba; Abdulrahman R Nurkamiden (Zaitun (Jurnal Ilmu Kesehatan), 2020)
Diabetes mellitus is a disease in which blood glucose (simple sugar) levels are high because the body cannot release or use insulin adequately. The objective of research was to determine the relationship of patient’s knowledge level about diabetes mellitus with the action to maintain blood glucose stability at Dungaliyo health center work area. The design used correlation descriptive with cross sectional method and the samples are 39 respondents which determinate with total sampling. The result analysis used chi-square statistical test with P value 0,001. Obtained there is significance relationship about patient’s knowledge level about diabetes mellitus with the action to maintain blood glucose stability. Expected to health officer at Dungaliyo health center will provide health education to increase patient’s knowledge level about diabetes mellitus.